2019
DOI: 10.1155/2019/4738237
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Dynamics Associated with Direct-Acting Antiviral Therapies in Naive and Experimented HCV Chronic-Infected Patients

Abstract: The therapeutic strategies used in the treatment of hepatitis C are essentially based on the combination of direct-acting antiviral agents (DAAs). This therapy has been shown to be very effective in relation to patient adherence to treatment and has shown high rates of sustained virological response (SVR). However, the immunological dynamics of patients infected with HCV is poorly understood. This fact led us to investigate the immune system of naive and experienced patients, who we followed before the therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(43 reference statements)
3
7
0
1
Order By: Relevance
“…Here, we have measured IFN-Ɣ and IL-2 production of lymphocytes stimulated in vitro, comparing the baseline and FUW12 samples of each patient and found that HCV clearance per se is not sufficient to reverse the decreased production of IFN-Ɣ and IL-2 by HCV-specific T cells, suggesting that prolonged exposure to HCV antigens leads to long-lasting HCV-specific T cells that lack effector functions. Thus, we could show that impaired HCV-specific CD4+ and CD8+ T cells responses during chronic HCV infection are not restored following successful HCV clearance, at least in the short-time after HCV elimination, which is in line with recent published studies [ 25 , 39 , 41 43 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Here, we have measured IFN-Ɣ and IL-2 production of lymphocytes stimulated in vitro, comparing the baseline and FUW12 samples of each patient and found that HCV clearance per se is not sufficient to reverse the decreased production of IFN-Ɣ and IL-2 by HCV-specific T cells, suggesting that prolonged exposure to HCV antigens leads to long-lasting HCV-specific T cells that lack effector functions. Thus, we could show that impaired HCV-specific CD4+ and CD8+ T cells responses during chronic HCV infection are not restored following successful HCV clearance, at least in the short-time after HCV elimination, which is in line with recent published studies [ 25 , 39 , 41 43 ].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the pro-inflammatory cytokines, it has been reported that NK and T cells produce high quantities of IFN-Ɣ and other pro-inflammatory cytokines during acute infections, while production is decreased during chronic infections [ 24 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of newer treatments against HCV, consisting of direct-acting antivirals (DDAs), promote a sustained virological response, leading to resolution of the HCV infection. However, although viremia eradication improves liver function, this seems not to be sufficient to completely reverse the cellular profile and production of cytokines, including IL-6, in patients with chronic disease, probably as a result of the change in the structure of the liver parenchyma that makes it impossible to recover homeostasis [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…When preexisting drug-resistant substitutions are not a factor, virologic failures to DAA therapy in this group of patients are still a matter of debate. Several factors have been considered as relevant for the success of DAA therapy, including immune reconstitution status, drug user addiction, and the extent of liver damage [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%